P‐6: The Effects of Buffer Layers on the Electrical Characteristics and Stability of Self‐Aligned Top‐Gate IGZO Thin Film Transistors. Issue 1 (May 2017) - Ho, Yi-Da; Yang, Yu-Xin; Yang, Ching-Fei; Li, Hung-Wei; Tsai, Chih-Hung; Lu, Hsueh-Hsing; Lin, Yu-Hsin
Abstract : The composition of buffer layer would be played a key role to affect the electrical performance and the reliability of the self‐aligned top‐gate a‐IGZO TFTs. In this work, the threshold voltage shift (ΔVth) of the device could be less than ±1V under positive and negative bias thermal illumination stress.